2011
DOI: 10.1080/10256016.2011.596625
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variations in the stable C isotope composition of dissolved inorganic carbon and in physico-chemical water parameters in the Plitvice Lakes system

Abstract: Plitvice Lakes waters were collected at 14 sampling points, including springs, tributaries and lakes, for the period 2002-2007. The results of the physical and chemical conditions of calcite precipitation as well as the δ(13)C values of dissolved inorganic carbon (DIC) were used to study the processes influencing calcite precipitation. Significant differences between spring, lake and stream waters as well as changes in the downstream direction were observed. The correlation between δ(13)C(DIC) values and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…Lower DIC concentrations in the lake center and outflow during summer (Table 1; Fig. 4a) might be the result of precipitation of carbonates as well as uptake of CO 2 or even HCO { 3 by photosynthetic organisms (Barešić et al 2011). For example, cyanobacteria that prevail in Lake Võ rtsjä rv in summer possess an environmental adaptation known as a CO 2 -concentrating mechanism that evolved to improve photosynthetic performance, particularly under CO 2 -limiting conditions (Price 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lower DIC concentrations in the lake center and outflow during summer (Table 1; Fig. 4a) might be the result of precipitation of carbonates as well as uptake of CO 2 or even HCO { 3 by photosynthetic organisms (Barešić et al 2011). For example, cyanobacteria that prevail in Lake Võ rtsjä rv in summer possess an environmental adaptation known as a CO 2 -concentrating mechanism that evolved to improve photosynthetic performance, particularly under CO 2 -limiting conditions (Price 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The exchange with the atmospheric CO 2 was also confirmed by the δ 13 C values of carbonate fractions: higher δ 13 C values of Lake Kozjak sediment, mean δ 13 C (−9 0 ± 0 4) , compared with the Lake Prošće δ 13 C (-9 7 ± 0 5) ( Table 1). δ 13 C values of DIC in Prošće and Kozjak Lake in the site of sampling were (−11 2 ± 1 2) and (−10 88 ± 0 64) , respectively [8]. The photosynthetic activity of aquatic plants could also influence the 14 C increase of DIC and carbonate fraction in downstream flow.…”
Section: Resultsmentioning
confidence: 99%
“…This was the result of the carbon origin and/or processes involved in sediment formations. The 14 C and δ 13 C values of carbonate fraction were the results of the geochemical processes occurred mainly in the karst spring/aquifier area [8,16]. Significantly higher 14 C of organic fraction for both lake sediments and δ 13 C values of −34 to −30 showed that the organic fraction was mainly composed of aquatic plants and influenced by bioproductivity of the lake waters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations